From Business to Care: An Analysis of Pharmaceutical Service Compliance Across Indonesian Pharmacies - Bethasari, Maulidwina (Majalah Kesehatan Indonesia, 2026)
Pharmaceutical services in Indonesian community pharmacies play a critical role in ensuring safe and effective medication use. However, despite the establishment of the Ministry of Health Regulation No. 73 of 2016, significant disparities in compliance persist, which may compromise patient safety and the quality of pharmaceutical care. This study analyzes pharmacy compliance across various regions of Indonesia in implementing pharmaceutical service standards, focusing on three key domains: pharmaceutical supply management, clinical services, and human resources. A total of 43 eligible studies were systematically reviewed and categorized according to the regulatory indicators. The results showed that pharmaceutical supply management demonstrated the highest compliance levels (average 88–94%), as it directly supports pharmacy profitability. In contrast, clinical services such as counseling, Home Pharmacy Care (HPC), and Drug Therapy Monitoring (DTM) exhibited low implementation rates (23–40%), primarily due to limited remuneration and insufficient pharmacist engagement. Only 36.87% of pharmacies conducted self-evaluations, yet these showed significantly higher compliance compared to those that did not. Pharmacist attendance alone did not correlate with improved clinical service provision, indicating that competency and institutional support are more critical determinants of compliance. In conclusion, the findings highlight that Indonesian pharmacies remain largely business-oriented, with clinical services underperformed relative to managerial aspects. Strengthening policy enforcement and professional capacity-building is essential to enhance compliance and support a shift toward patient-centered pharmaceutical care.